2022
DOI: 10.1017/s1041610222000527
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards dementia among Chinese adults aged 50 years and older: a comparative study of immigrants living in Melbourne and nonimmigrants living in Beijing

Abstract: Objectives: This study investigated attitudes towards dementia among Chinese immigrants aged 50 years and over living in Australia and compares these attitudes with those of individuals living in mainland China. It aimed to better understand what older Chinese adults think about dementia and to inform the development of tailored dementia-related services for this group of people. Design: A qualitative design involving individual interviews was employed in this study. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The Tripartite Model of Attitudes has been widely used in various research fields, including social psychology, consumer behavior, and health behavior [16,17]. It provides a comprehensive framework for understanding the formation and expression of attitudes, considering the affective, behavioral, and cognitive aspects that contribute to individuals' attitudes and subsequent actions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The Tripartite Model of Attitudes has been widely used in various research fields, including social psychology, consumer behavior, and health behavior [16,17]. It provides a comprehensive framework for understanding the formation and expression of attitudes, considering the affective, behavioral, and cognitive aspects that contribute to individuals' attitudes and subsequent actions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This can lead to feelings of shame, embarrassment, or isolation. In general, we find that common terms for dementia focus on the condition as a “normal part of aging,” “insanity,” “crazy,” and “mental illness.” The disease can also label as “evil,” “an act of God,” “a divine test,” “punishment,” “one’s bad karma,” or “the work of spirits and demons” ( 34 , 46–48 ). Such terminologies are likely to contribute to feelings of humiliation, dread, and disgrace and causes individuals to avoid discussing their symptoms and conceal them ( 34 ).…”
Section: Stigma and Dementia Within Cald Communitiesmentioning
confidence: 99%
“…Findings from cross-cultural comparisons are helpful for the understanding the effect of crosscountry immigration experiences and social-cultural changes on immigrants' attitudes towards dementia. Zhao and colleagues compared attitudes towards dementia between older Chinese immigrants living in Melbourne, Australia, and older Chinese adults living in Beijing, China (Zhao et al, 2022). They found that both populations held negative feelings, stigmatized beliefs, and negative stereotypes of dementia.…”
mentioning
confidence: 99%